Investigation of fibrinogen in early bleeding of patients with newly diagnosed acute promyelocytic leukemia. (4th July 2021) - Chu, Tiantian; Wang, Hong; Lv, Xin; Qi, Jiaqian; Tang, Yaqiong; Fan, Yi; Qiu, Huiying; Tang, Xiaowen; Fu, Chengcheng; Ruan, Changgeng; Han, Yue; Wu, De-Pei
Abstract: Early hemorrhagic death remains a major cause of treatment failure in acute promyelocytic leukemia (APL). This study investigated the role of fibrinogen concentrations in early hemorrhage and overall survival (OS) of APL patients. Laboratory and clinical data, including fibrinogen concentrations and other coagulation indexes, bleeding events, and survival data, of 198 patients newly diagnosed with APL from February 2012 to December 2017 were extracted from patient records and retrospectively investigated. Patients with moderate/severe bleeding had significantly lower median fibrinogen concentrations ( p = .023), higher Chinese disseminated intravascular coagulation scoring system (CDSS) ( p < .001), and were more often female ( p = .034) than patients with no such bleeding. Additionally, patients with fibrinogen <1.0 g/L and 1.0–1.6 g/L had significantly higher moderate/severe bleeding rates than those with fibrinogen >1.6 g/L ( p = .015; p = .023). However, moderate/severe ( p = .088) and severe bleeding rates ( p = .063) were comparable for patients with fibrinogen <1.0 g/L and 1.0–1.6 g/L. Multivariate analysis showed that fibrinogen ≤1.6 g/L ( p = .036), platelet counts ≤10 × 10 9 /L ( p = .037), and CDSS scores ≥5 ( p = .023) were independent risk factors for moderate/severe bleeding. Survival analysis indicated that moderate/severe bleeding ( p = .018), fibrinogen ≤1.6 g/L combined with prothrombin time >12.8 s ( p = .005), age ≥60 years ( p = .001), and CDSS ≥5 ( p = .044) were independent predictors of 1-year OS. Fibrinogen ≤1.6 g/L may be an independent risk factor for early bleeding in newly treated patients with APL and is associated with a worse 1-year OS. Increasing fibrinogen to >1.6 g/L may help to prevent bleeding.